Expansion Planning of Electricity Generating System Using the VALORAGUA and WASP-IV Models in Nepal - Shrestha, Jayandra Prasad; Shrestha, Namrata Tusuju (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
This paper presents a framework for a possible expansion plan of Nepal’s electricity generation system using VALORAGUA and Wien Automatic System Planning (WASP-IV) models as examples. Given that Nepal seeks to add several hydropower plants to the Integrated National Power System (INPS) in the next few years, this type of planning is crucial. To explore potential expansion plans, the 48 hydropower plants (20 of which are currently operating) within 18 hydro networks and two diesel plants are included, and different options such as the possibility of export, seasonal variations in hydrology, and projected growth rates in gross domestic product are considered. The results illustrate the long run marginal cost (LRMC) and loss of load probability (LoLP) through 2030 in Nepal. It is found that LRMC is 3.50 Nepali Rupees per kilowatt hour at 4.1% of average LoLP. While scrutinizing the results, it is found that LoLP is higher in early stage of projections due to generation capacity limitations from 2014 to 2016. However, by the end of 2017, the LRMC and LoLP begin to decrease significantly. On this premise, the model suggests to introduce large storage plants for hydropower generation and export of that excess energy. Furthermore, a proper implementation of proposed peaking and storage plants to meet rising demand can offset the need to obtain electricity through more expensive and less environmentally-friendly means such as thermal/diesel plants. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 45-51